Pengembangan Buku Ajar Bahasa Arab Berbasis QR Code pada Mahārah Istimā’ bagi Mahasiswa Non-PBA - Aisa, Aufia; Imansyah, Bima; Rahmawati, Rina Dian (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This research was motivated by the need for more interest from non-Arabic students in mastering Arabic language learning, especially listening skills. This is because the learning process could be more effective regarding learning methods and the teaching materials that serve as references. Therefore, this research was conducted to develop a QR Code-based Arabic language textbook to overcome the lack of mastery of Arabic listening skills. The method used in this research is R&D, which applies the Borg and Gall model. The subjects in this research were students from the Management Study Program at KH University. A. Wahab Hasbullah Jombang, totaling 22 students. The data instruments used are interviews, questionnaires and tests. The data analyzed produce qualitative and quantitative data, including 1) teaching materials developed in Arabic language textbooks based on QR Code innovation for Istima's learning. 2) based on the validity test, the textbook developed achieved a very valid feasibility level with an average of 94.00% from media experts and 88.08% from media experts. 3) the level of effectiveness of textbooks is very effective as seen from the analysis using the paired t test which obtained a significant value of 0.00 < 0.05 so it can be said that there is an influence on the use of textbooks.